Identifying Blockchain Technologies in the Protection of Sensitive Information on Social Networks: A Systematic Review - Huaman Obregon, José María (2025)
This work addresses the identification of blockchain-based technologies for the protection of sensitive data on digital platforms that are now part of our daily lives. It points out the most relevant blockchain technologies that are gaining ground in the technological era in which we find ourselves. The methodology used corresponds to the principles of the PRISMA declaration, using high-demand repositories such as SCOPUS, SCIELO, IEEE XPLORE, MDPI, IIETA, SAGE JOURNAL and IJCSE, finding 25 documents relevant to the study. The latter focus their research on the use and application of blockchain technologies in specific cases of digital platforms, highlighting 4 technologies: Hybrid blockchain, Smart contracts, Public blockchain and Data encryption. The results indicate that they are the most used technologies for the protection of information. The conclusions highlight the importance of Blockchain in protection. information, indicating opportunities for future research are identified, in particular more specific case studies where much better use is made of the technology in question.